Non-Invasive Skin Imaging Assessment of Human Stress During Head-Down Bed Rest Using a Portable Handheld Two-Photon Microscope - Wang, Junjie; Zhen, Zhen; Wang, Yanqing; Wu, Runlong; Hu, Yanhui; Fu, Qiang; Li, Yongzhi; Xin, Bingmu; Song, Jinping; Li, Jianwei; Ren, Yafei; Feng, Lishuang; et al. (Frontiers in Physiology, 2022)
Spaceflight presents a series of physiological and pathological challenges to the astronauts which result from ionizing radiation, microgravity, isolation, and other spaceflight hazards. These risks cause a series of aging-related diseases which are associated with increasing oxidative stress and mitochondria dysfunction. Skin contains many autofluorescent substances such as nicotinamide adenine dinucleotide phosphate (NAD(P)H), keratin, melanin, elastin, and collagen, which reflect physiological and pathological changes in vivo. In this study, we used the portable handheld two-photon microscope to conduct high-resolution in vivo skin imaging on volunteers during 15 days of head-down bed rest. The two-photon microscope equipped with a flexible handheld scanning head was used to measure two-photon excited fluorescence (TPEF) and second harmonic generation (SHG) images of left forearm, left front chest, and forehead of volunteers. Changes in TPEF, SHG and the SHG-to-TPEF aging index of dermis (SAAID) were measured. It was found that TPEF intensity increased in bed rest and restore to the normal level after recovery. Meantime, SHG increased slightly in bed rest, and the skin aging index increased. Moreover, we found the skin TPEF signals of the left forearm were significantly negative associated with oxidative stress marker malondialdehyde (MDA) and DNA damage marker 8-hydroxy-2'-desoxyguanosine (8-OHdG) values of subjects during head-down bed rest, respectively. Meantime, the SHG signals were also significant negative correlation with MDA and 8-OHDG. And the significant negative correlation between SAAID of left chest and serum antioxidant superoxide dismutase (SOD) levels were found. These results demonstrated the skin autofluorescence signals could reflect the changes of human oxidant status. This study provides evidence for in-orbit monitoring the change of human stress using portable handheld two-photon microscope for skin imaging.